Iridium ruthenium tin composite catalyst and preparation method and application thereof
By developing iridium ruthenium tin composite catalyst, the problem of high amount of precious metals used by the anode catalyst in the prior art has been solved, higher catalytic activity and stability have been achieved, cost has been reduced, and the sustainable development of proton exchange membrane electrolysis hydrogen production technology has been promoted.
Patent Information
- Application Number
- CN202311110491.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-08-30
AI Technical Summary
In the existing proton exchange membrane electrolytic hydrogen production technology, the precious metal iridium of the anode catalyst is used in large quantities, resulting in high costs, limiting the large-scale application of this technology.
A iridium ruthenium tin composite catalyst is developed, which contains amorphous oxides of iridium, ruthenium and tin. Its catalytic activity and stability are improved through specific synthesis methods and conditions and the amount of precious metals is reduced.
The iridium ruthenium tin composite catalyst has higher catalytic activity and stability than commercial iridium oxide catalysts, significantly reducing the amount and cost of precious metals, and improving the efficiency of hydrogen production by electrolyzing water.
Smart Images

Figure CN119549145A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the fields of hydrogen energy and chemical industry, and in particular, to an iridium, ruthenium, and tin composite catalyst and a preparation method and application thereof. Background Art
[0002] Compared with alkaline water electrolysis technology, proton exchange membrane water electrolysis hydrogen production technology has the advantages of fast response speed, large current density, wide working load range, and high hydrogen purity. In particular, it has unparalleled advantages in the field of using renewable energy to generate electricity and then electrolyze water to produce hydrogen. It is the main way to obtain green hydrogen in the future. The anode catalyst is one of the key materials for proton exchange membrane water electrolysis hydrogen production and is the main rate-controlling step for PEM water electrolysis hydrogen production. At present, commercial PEM water electrolysis devices basically use iridium oxide or iridium black catalysts. The price of precious metal iridium is expensive (~1,000 yuan / g), and the dosage reaches 1-2 mg / cm 2 Therefore, reducing the amount of iridium in the anode is one of the important breakthroughs for the large-scale application of PEM water electrolysis. There are two strategies to reduce the amount of iridium: one is to increase the electrochemical intrinsic activity of the catalyst, so that only a small amount of catalyst is needed to achieve the same performance; the other is to increase the utilization rate of the active components. Summary of the invention
[0003] The purpose of the present invention is to provide an iridium ruthenium tin composite catalyst and a preparation method and application thereof. The iridium ruthenium tin composite catalyst has higher catalytic activity than a commercial iridium oxide catalyst, and the amount of precious metal used is significantly reduced, the cost is reduced, and it has greater use value.
[0004] In order to achieve the above-mentioned purpose, the first aspect of the present disclosure provides an iridium ruthenium tin composite catalyst, which comprises iridium, ruthenium and tin elements, and the XRD spectrum of the iridium ruthenium tin composite catalyst only shows an amorphous peak package between 25 and 40°.
[0005] Optionally, the O1s characteristic peak of the XPS spectrum of the iridium, ruthenium, and tin composite catalyst contains a MO characteristic peak and an M-OH characteristic peak, and B defined by the following formula (1) 0 Any value between 0.4 and 0.5;
[0006] B 0 =B 1 / (B 1 +B 2 ) Formula (1);
[0007] Among them, B 1 is the peak area of the M-OH characteristic peak in the XPS spectrum of the iridium ruthenium tin composite catalyst; 2 It is the peak area of the MO characteristic peak in the XPS spectrum of the iridium ruthenium tin composite catalyst.
[0008] Optionally, the BET specific surface area of the iridium ruthenium tin composite catalyst is 60 to 80 m 2 / g, particle size is 3 to 8 nm.
[0009] Optionally, the chemical composition of the iridium ruthenium tin composite catalyst is Ir x Ru y Sn 1-x-y O 2 ; Wherein, x is any value between 0.4 and 0.6, and y is any value between 0.1 and 0.2.
[0010] Optionally, the XRD spectrum of the iridium, ruthenium, and tin composite catalyst does not contain IrO 2 、RuO 2 and SnO 2 diffraction peaks of the crystal plane.
[0011] A second aspect of the present disclosure provides a method for preparing an iridium, ruthenium, and tin composite catalyst, the method comprising the following steps:
[0012] S1, mixing an iridium source, a ruthenium source, a tin source, a complexing agent and water, and reacting the resulting mixture to obtain a first material; wherein the pH of the mixture is 5 to 9, and the complexing agent is selected from C4 to C8 organic polyacids and soluble salts of C4 to C8 organic polyacids;
[0013] S2, separating the water in the first material to obtain an iridium ruthenium tin composite catalyst precursor;
[0014] S3. calcining the iridium ruthenium tin composite catalyst precursor in an oxygen-containing atmosphere.
[0015] Optionally, step S1 includes the following steps:
[0016] S1-1, mixing the iridium source, the first complexing agent and water for the first time and adjusting the pH to 5 to 9, preferably 7 to 8, to obtain a first mixture;
[0017] S1-2, mixing the ruthenium source, the second complexing agent and water for a second time and adjusting the pH to 5 to 9, preferably 7 to 8, to obtain a second mixture;
[0018] S1-3, mixing the tin source, the third complexing agent and water for a third time and adjusting the pH to 5 to 9, preferably 7 to 8, to obtain a third mixture;
[0019] S1-4, mixing the first mixture, the second mixture and the third mixture to obtain the mixed material.
[0020] Optionally, the iridium source is selected from one or more of chloroiridic acid and chloroiridic acid alkali metal salts; preferably, the chloroiridic acid alkali metal salt is selected from one or two of potassium chloroiridate and sodium chloroiridate;
[0021] The ruthenium source is a soluble salt of ruthenium, preferably one or both of ruthenium trichloride and ruthenium acetate;
[0022] The tin source is a soluble salt of tin and / or a soluble alkali metal stannate, preferably one or both of tin tetrachloride and sodium stannate.
[0023] Optionally, the first complexing agent, the second complexing agent and the third complexing agent are the same or different, and are independently selected from one or more of citric acid, tartaric acid, malic acid, succinic acid, sodium citrate, sodium tartrate, sodium malate and sodium succinate;
[0024] Preferably, the molar ratio of the first complexing agent to the iridium source is 1.5 to 2.5:1, preferably 1.8 to 2.2:1;
[0025] Preferably, the molar ratio of the second complexing agent to the ruthenium source calculated as ruthenium is 1 to 2:1, preferably 1.5 to 1.8:1;
[0026] Preferably, the molar ratio of the third complexing agent to the tin source calculated as tin is 2 to 3:1, preferably 2.2 to 2.7:1.
[0027] Optionally, in step S1, the molar ratio of the iridium source calculated as iridium, the tin source calculated as tin, and the ruthenium source calculated as ruthenium is (2-6):(1-5):1.
[0028] Optionally, in step S1, the reaction conditions include: temperature of 50 to 80° C., preferably 60 to 70° C.; reaction time of 0.5 to 4 h, preferably 1 to 2 h;
[0029] Optionally, in step S1, the pH of the mixed material is 7 to 8;
[0030] Optionally, a pH regulator is added to adjust the pH of the mixed material. Optionally, the pH regulator is selected from one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide and ammonia water.
[0031] Optionally, in step S3, the conditions for the calcination treatment include: a calcination temperature of 300 to 400° C., preferably 340 to 370° C.; and a calcination time of 1 to 3 hours.
[0032] Optionally, the method further comprises: washing the product obtained by the calcination treatment; the solvent used in the washing treatment is a mixed solution of alcohol and water, and the alcohol accounts for 10 to 95% by weight of the mixed solution, preferably 30 to 60% by weight;
[0033] Preferably, the alcohol is selected from one or more of methanol, ethanol, n-propanol and isopropanol.
[0034] The third aspect of the present disclosure provides an iridium ruthenium tin composite catalyst prepared by the method described in the second aspect of the present disclosure.
[0035] The fourth aspect of the present disclosure provides use of the iridium, ruthenium, tin composite catalyst described in the first aspect of the present disclosure and the third aspect of the present disclosure in producing hydrogen by electrolysis of water.
[0036] Through the above technical scheme, the present disclosure provides an iridium ruthenium tin composite catalyst and a preparation method and application thereof. The iridium ruthenium tin composite catalyst comprises amorphous oxides of iridium, ruthenium and tin, and only an amorphous peak package appears in the XRD spectrum, and there is no obvious crystalline diffraction peak. When used as an anode catalyst for proton exchange membrane water electrolysis to produce hydrogen, it has better stability than a ruthenium catalyst, higher catalytic activity than a commercial iridium oxide catalyst, and the amount of precious metal used is significantly reduced, and the cost is significantly reduced.
[0037] In addition, in the preparation process, the present invention uses a complexing agent to mix with the iridium source, ruthenium source and tin source, which can improve the uniformity of the dispersion of the iridium source, ruthenium source and tin source in the mixed solution; and the present invention uses C4-C8 organic polyacids and soluble salts of C4-C8 organic polyacids as complexing agents, which can avoid precipitation in the solution. The reaction process does not use strong corrosive solvents such as hydrochloric acid, and the preparation method is simple to operate and the conditions are mild.
[0038] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0040] Figure 1 is the XRD pattern of the catalyst in Example 1 of the present disclosure.
[0041] Figure 2 This is the TEM spectrum of the catalyst in Example 1 of the present disclosure.
[0042] Figure 3 It is the O1s XPS spectrum of the catalyst in Example 1 of the present disclosure. DETAILED DESCRIPTION
[0043] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0044] A first aspect of the present disclosure provides an iridium ruthenium tin composite catalyst, which comprises iridium, ruthenium and tin elements, and an XRD spectrum of the iridium ruthenium tin composite catalyst shows an amorphous peak package only between 25 and 40 degrees.
[0045] The iridium ruthenium tin composite catalyst provided by the present invention comprises iridium, ruthenium and tin elements, and only an amorphous peak package appears in the XRD spectrum, and no obvious crystalline diffraction peak exists. When used as an anode catalyst for hydrogen production by proton exchange membrane water electrolysis, it has higher catalytic activity than commercial iridium oxide catalysts, and the amount of precious metals used is significantly reduced, and the cost is significantly reduced.
[0046] In the present disclosure, "peak envelope" in the XRD spectrum refers to other forms of protrusions that appear in the XRD spectrum in addition to the obvious and sharp characteristic peaks conventionally recognized by technicians in this field. The "peak envelope" generally has the characteristics of low intensity and large width.
[0047] According to one embodiment of the present disclosure, the XRD spectrum of the iridium, ruthenium, and tin composite catalyst does not contain IrO 2 、RuO 2 and SnO 2 The iridium, ruthenium and tin elements in the iridium, ruthenium and tin composite catalyst provided by the present invention exist in the form of amorphous oxides, and IrO does not appear in the XRD spectrum. 2 、RuO 2 and SnO 2 Crystal plane diffraction peaks of three substances.
[0048] According to one embodiment of the present disclosure, the chemical composition of the iridium ruthenium tin composite catalyst is Ir x Ru y Sn 1-x- y O 2 ; wherein x is any value between 0.4 and 0.6, and y is any value between 0.1 and 0.2. In the present disclosure, the chemical composition of the catalyst is determined by X-ray fluorescence analysis (XRF analysis). The chemical composition of the catalyst is consistent with the raw material addition ratio during preparation. The chemical composition described in the present disclosure is only used as a schematic representation.
[0049] According to one embodiment of the present disclosure, the O1s characteristic peak of the XPS spectrum of the iridium, ruthenium, and tin composite catalyst contains a MO characteristic peak and an M-OH characteristic peak, and B defined by the following formula (1): 0 Any value between 0.4 and 0.5;
[0050] B 0 =B 1 / (B 1 +B 2 ) Formula (1);
[0051] Among them, B 1 is the peak area of the M-OH characteristic peak in the XPS spectrum of the iridium ruthenium tin composite catalyst; 2 is the peak area of the MO characteristic peak in the XPS spectrum of the iridium ruthenium tin composite catalyst. The inventors have found in experiments that when the B 1 / (B 1 +B 2 ) ratio is within the range of this embodiment, it can have a lower overpotential and a higher oxygen evolution activity.
[0052] According to one embodiment of the present disclosure, the BET specific surface area of the iridium, ruthenium, and tin composite catalyst is 60 to 80 m 2 / g, and the particle size is 3 to 8 nm, preferably 4 to 6 nm. In the present disclosure, the particle size of the catalyst particles refers to the particle size of the catalyst particles measured by transmission electron microscopy. For example, "the particle size of the catalyst particles is 3 to 8 nm" means that the particle size of each particle in the transmission electron microscopy spectrum of the catalyst particles is within the range of 3 to 8 nm.
[0053] A second aspect of the present disclosure provides a method for preparing an iridium, ruthenium, and tin composite catalyst, the method comprising the following steps:
[0054] S1, mixing an iridium source, a ruthenium source, a tin source, a complexing agent and water, and reacting the resulting mixture to obtain a first material; wherein the pH of the mixture is 5 to 9, and the complexing agent is selected from C4 to C8 organic polyacids and soluble salts of C4 to C8 organic polyacids;
[0055] S2, separating the water in the first material to obtain an iridium ruthenium tin composite catalyst precursor;
[0056] S3. calcining the iridium ruthenium tin composite catalyst precursor in an oxygen-containing atmosphere.
[0057] According to an embodiment of the present disclosure, step S1 includes the following steps:
[0058] S1-1, mixing the iridium source, the first complexing agent and water for the first time and adjusting the pH to 5 to 9, preferably 7 to 8, to obtain a first mixture;
[0059] S1-2, mixing the ruthenium source, the second complexing agent and water for a second time and adjusting the pH to 5 to 9, preferably 7 to 8, to obtain a second mixture;
[0060] S1-3, mixing the tin source, the third complexing agent and water for a third time and adjusting the pH to 5 to 9, preferably 7 to 8, to obtain a third mixture;
[0061] S1-4, mixing the first mixture, the second mixture and the third mixture to obtain the mixed material. The above implementation can improve the uniformity of the dispersion of the iridium source, the ruthenium source and the tin source in the mixed material; at the same time, precipitation in the solution can be avoided; the reaction process does not use highly corrosive solvents such as hydrochloric acid, providing a preparation method that is easy to operate and has mild conditions.
[0062] According to one embodiment of the present disclosure, the iridium source is selected from one or more of chloroiridic acid and chloroiridic acid alkali metal salts; preferably, the chloroiridic acid alkali metal salt is selected from one or both of potassium chloroiridic acid and sodium chloroiridic acid; the chloroiridic acid may or may not contain crystal water, generally containing crystal water (such as having the formula H 2 IrCl 6 6H 2 O); the ruthenium source is a soluble salt of ruthenium, preferably one or both of ruthenium trichloride and ruthenium acetate; the tin source is a soluble salt of tin and / or a soluble alkali metal stannate, preferably one or both of tin tetrachloride or sodium stannate.
[0063] According to one embodiment of the present disclosure, the first complexing agent, the second complexing agent and the third complexing agent are the same or different, and are independently selected from one or more of citric acid, tartaric acid, malic acid, succinic acid, sodium citrate, sodium tartrate, sodium malate and sodium succinate;
[0064] Preferably, the molar ratio of the first complexing agent to the iridium source is 1.5 to 2.5:1, preferably 1.8 to 2.2:1;
[0065] Preferably, the molar ratio of the second complexing agent to the ruthenium source calculated as ruthenium is 1 to 2:1, preferably 1.5 to 1.8:1;
[0066] Preferably, the molar ratio of the third complexing agent to the tin source is 2 to 3: 1, preferably 2.2 to 2.7: 1. The above embodiment can avoid precipitation in the solution, and is conducive to the catalyst having a lower overpotential and higher oxygen evolution activity.
[0067] According to an embodiment of the present disclosure, in step S1, the molar ratio of the iridium source calculated as iridium, the tin source calculated as tin, and the ruthenium source calculated as ruthenium is (2-6): (1-5): 1. The above embodiment is conducive to the catalyst having a lower overpotential and higher oxygen evolution activity.
[0068] According to one embodiment of the present disclosure, in step S1, the reaction conditions include: temperature of 50 to 80° C., preferably 60 to 70° C.; reaction time of 0.5 to 4 h, preferably 1 to 2 h;
[0069] Optionally, in step S1, the pH of the mixed material is 7 to 8;
[0070] Optionally, a pH regulator is added to adjust the pH of the mixed material. Optionally, the pH regulator is selected from one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide and ammonia water.
[0071] According to an embodiment of the present disclosure, in step S3, the conditions of the calcination treatment include: a calcination temperature of 300 to 400° C., preferably 340 to 370° C.; and a calcination time of 1 to 3 hours.
[0072] According to an embodiment of the present disclosure, the method further comprises: washing the product obtained by the roasting treatment; the solvent used in the washing treatment is a mixed solution of alcohol and water, the alcohol accounts for 10 to 95% by weight of the mixed solution, preferably 30 to 60% by weight; preferably, the alcohol is selected from one or more of methanol, ethanol, n-propanol and isopropanol. In the above preferred embodiment, it is easier to separate the catalyst by centrifugation.
[0073] The third aspect of the present disclosure provides an iridium ruthenium tin composite catalyst prepared by the method described in the second aspect of the present disclosure.
[0074] The fourth aspect of the present disclosure provides use of the iridium, ruthenium, tin composite catalyst described in any one of the first aspect of the present disclosure or the third aspect of the present disclosure in producing hydrogen by electrolysis of water.
[0075] The present disclosure is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present disclosure, but are not intended to limit the present disclosure in any form.
[0076] The raw materials used in the examples were all commercially available and were analytically pure unless otherwise specified. Chloroiridic acid or alkali metal chloroiridic acid salt was prepared as an aqueous solution with a concentration of 0.182 mol / L for use, or as a solution with a higher concentration for use.
[0077] Instruments, methods and conditions for TEM analysis: The model of the high-resolution transmission electron microscope (HRTEM) used in the present invention is JEM-2100 (HRTEM) (Japan Electron Co., Ltd.), and the test conditions of the high-resolution transmission electron microscope are: the acceleration voltage is 200 kV.
[0078] The model of the X-ray fluorescence spectrometer (XRF) is Rigaku 3013 X-ray fluorescence spectrometer, and the X-ray fluorescence spectrometry analysis test conditions are: scanning time is 100 s, and the atmosphere is air.
[0079] The present disclosure detects the elements on the surface of the material by X-ray photoelectron spectroscopy (XPS). The X-ray photoelectron spectroscopy used is an ESCALab220i-XL X-ray electron spectrometer equipped with Avantage V5.926 software produced by VG Scientific. The X-ray photoelectron spectroscopy analysis test conditions are as follows: the excitation source is monochromatic A1Kα X-ray, the power is 330W, and the basic vacuum during the analysis test is 3×10 -9 In addition, the electron binding energy was calibrated using the C1s peak (284.3 eV) of elemental carbon.
[0080] BET test method: In the present disclosure, the pore structure properties of the samples are measured by a Quantachrome AS-6B analyzer, and the specific surface area of the catalyst is obtained by the Brunauer-Emmett-Taller (BET) method.
[0081] X-ray diffraction analysis (XRD) was carried out on a Shimadzu XRD-6000 X-ray diffractometer, Japan, with the test conditions including: tube voltage 40 kV, tube current 40 mA, Cu target Kα radiation, and 2θ scanning range of 5° to 80°.
[0082] The electrochemical workstation model is PARSTAT3000A-DX, and the rotating disk electrode model is 636A. A three-electrode system is used, with a saturated calomel electrode as the reference electrode, a platinum sheet as the counter electrode, and a glassy carbon electrode as the working electrode. The electrolyte used under acidic conditions is 0.5MH 2 SO 4 The catalyst to be tested was ultrasonically dispersed in a mixed solution of isopropanol, water and Nafion, and then dropped onto the surface of the glassy carbon electrode. After natural drying, the working electrode was obtained. The catalyst loading was 0.38 mg cm -2 The test temperature was 25°C. Oxygen was passed through the solution for 30 minutes before the test to saturate the solution with oxygen. The rotation speed was 2500rpm. The scanning range of the linear polarization curve was 1.2-1.5V (vs RHE) and the scanning rate was 5mV / s. The scanning range of the stability test was 1.26V-1.56V (vs RHE), the scanning rate was 50mV / s, and the number of scanning circles was 10,000.
[0083] Example 1 Catalyst Ir 0.6 Ru 0.1 Sn 0.3 O 2 Preparation
[0084] (1) taking 20 mL (3.64 mmol) of chloroiridic acid aqueous solution, weighing 1.05 g (5.47 mmol) of citric acid, stirring and mixing at room temperature, and adjusting the pH of the solution to between 7 and 8; wherein the molar ratio of the first complexing agent to the iridium source in terms of iridium is 1.5:1;
[0085] (2) weighing 0.13 g (0.62 mmol) of ruthenium trichloride and dissolving it in 5 ml of water, weighing 0.12 g (0.62 mmol) of citric acid, stirring and mixing at room temperature, and adjusting the pH of the solution to between 7 and 8; wherein the molar ratio of the second complexing agent to the ruthenium source in terms of ruthenium is 1:1;
[0086] (3) Weigh Na 2 SnO 3 ·3H 2 O 0.48g (1.82mmol) is dissolved in 10ml water, citric acid 0.87g (4.53mmol) is weighed, and after stirring and mixing at room temperature, the pH of the solution is adjusted to between 7 and 8; wherein the molar ratio of the third complexing agent to the tin source calculated in tin is 2.5:1; the molar ratio of the iridium source calculated in iridium, the tin source calculated in tin and the ruthenium source calculated in ruthenium is 6:3:1.
[0087] (4) mixing the three solutions of steps (1) to (3) and reacting them at 70° C. for 1 h;
[0088] (5) After cooling, spin-dry at 70°C and dry in an oven at 120°C for 8 h;
[0089] (6) After the catalyst is taken out and cooled, it is ground and laid flat on a porcelain boat. In an air atmosphere, the temperature is increased to 330°C at a rate of 2°C / min and maintained for 2 h.
[0090] (7) Cool to room temperature, add a certain amount of deionized water for ultrasonic washing and centrifugation (10000 rpm, 10 min), then wash with a 1:1 mixed solvent of ethanol and water and centrifuge for 3 times (pH test paper detection is neutral), and place the centrifuge tube containing the catalyst in a forced air drying oven (60°C) for 12 h. The obtained catalyst product is recorded as CAT-1.
[0091] XRF test analysis shows that the chemical composition of CAT-1 is Ir 0.6 Ru 0.1 Sn 0.3 O 2 The XRD pattern of CAT-1 is as follows: Figure 1 As shown in the figure, it can be seen that only a weak amorphous peak appears near 25-40°. TEM test analysis shows that the particle size of CAT-1 is 3-5nm.
[0092] Example 2 Catalyst Ir 0.5 Ru 0.1 Sn 0.4 O 2 Preparation
[0093] (1) taking 20 mL (3.64 mmol) of chloroiridic acid aqueous solution, weighing 1.05 g (5.47 mmol) of citric acid, stirring and mixing at room temperature, and adjusting the pH of the solution to between 7 and 8; wherein the molar ratio of the first complexing agent to the iridium source in terms of iridium is 1.5:1;
[0094] (2) weighing 0.15 g (0.73 mmol) of ruthenium trichloride and dissolving it in 5 ml of water, weighing 0.15 g (0.78 mmol) of citric acid, stirring and mixing at room temperature, and adjusting the pH of the solution to between 7 and 8; wherein the molar ratio of the second complexing agent to the ruthenium source in terms of ruthenium is 1.1:1;
[0095] (3) Weigh Na 2 SnO 3 ·3H 2 O 0.78g (2.91mmol) is dissolved in 10ml water, citric acid 1.40g (7.29mmol) is weighed, and after stirring and mixing at room temperature, the pH of the solution is adjusted to between 7 and 8; wherein the molar ratio of the third complexing agent to the tin source calculated in tin is 2.5:1; the molar ratio of the iridium source calculated in iridium, the tin source calculated in tin and the ruthenium source calculated in ruthenium is 5:4:1.
[0096] (4) mixing the three solutions of steps (1) to (3) and reacting them at 70° C. for 1 h;
[0097] (5) After cooling, spin-dry at 70°C and dry in an oven at 120°C for 8 h;
[0098] (6) After the catalyst is taken out and cooled, it is ground and laid flat on a porcelain boat. In an air atmosphere, the temperature is increased to 330°C at a rate of 2°C / min and maintained for 2 h.
[0099] (7) Cool to room temperature, add a certain amount of deionized water for ultrasonic washing and centrifugation (10000 rpm, 10 min), then wash with a 1:1 mixed solvent of ethanol and water and centrifuge for 3 times (pH test paper detection is neutral), and place the centrifuge tube containing the catalyst in a forced air drying oven (60°C) for 12 h. The obtained catalyst product is recorded as CAT-2.
[0100] XRF test analysis shows that the chemical composition of CAT-2 is Ir 0.5 Ru 0.1 Sn 0.4 O2 .
[0101] Example 3 Catalyst Ir 0.4 Ru 0.2 Sn 0.4 O 2 Preparation
[0102] (1) taking 20 mL (3.64 mmol) of chloroiridic acid aqueous solution, weighing 1.05 g (5.47 mmol) of citric acid, stirring and mixing at room temperature, and adjusting the pH of the solution to between 7 and 8; wherein the molar ratio of the first complexing agent to the iridium source in terms of iridium is 1.5:1;
[0103] (2) weighing 0.38 g (1.83 mmol) of ruthenium trichloride and dissolving it in 5 ml of water, weighing 0.36 g (1.88 mmol) of citric acid, stirring and mixing at room temperature, and adjusting the pH of the solution to between 7 and 8; wherein the molar ratio of the second complexing agent to the ruthenium source in terms of ruthenium is 1:1;
[0104] (3) Weigh Na 2 SnO 3 ·3H 2 0.97 g (3.64 mmol) of O is dissolved in 10 ml of water, 1.75 g (9.11 mmol) of citric acid is weighed, and after stirring and mixing at room temperature, the pH of the solution is adjusted to between 7 and 8; wherein the molar ratio of the third complexing agent to the tin source calculated in terms of tin is 2.5:1; the molar ratio of the iridium source calculated in terms of iridium, the tin source calculated in terms of tin, and the ruthenium source calculated in terms of ruthenium is 2:2:1
[0105] (4) mixing the three solutions of steps (1) to (3) and reacting them at 70° C. for 1 h;
[0106] (5) After cooling, spin-dry at 70°C and dry in an oven at 120°C for 8 h;
[0107] (6) After the catalyst is taken out and cooled, it is ground and laid flat on a porcelain boat. In an air atmosphere, the temperature is increased to 330°C at a rate of 2°C / min and maintained for 2 h.
[0108] (7) Cool to room temperature, add a certain amount of deionized water for ultrasonic washing and centrifugation (10000 rpm, 10 min), then wash with a 1:1 mixed solvent of ethanol and water and centrifuge for 3 times (pH test paper detection is neutral), and place the centrifuge tube containing the catalyst in a forced air drying oven (60°C) for 12 h. The obtained catalyst product is recorded as CAT-3.
[0109] XRF test analysis shows that the chemical composition of CAT-3 is Ir 0.4 Ru 0.2 Sn0.4 O 2 .
[0110] Example 4 Catalyst Ir 0.6 Ru 0.1 Sn 0.3 O 2 Preparation
[0111] The catalyst was prepared by the same method as in Example 1, except that:
[0112] (1) taking 20 mL (3.64 mmol) of potassium chloroiridate aqueous solution, weighing 0.82 g (5.47 mmol) of tartaric acid, stirring and mixing at room temperature, and adjusting the pH of the solution to between 7 and 8; wherein the molar ratio of the first complexing agent to the iridium source in terms of iridium is 1.5:1;
[0113] (2) weighing 0.15 g (0.62 mmol) of ruthenium acetate and dissolving it in 5 ml of water, weighing 0.83 g (0.62 mmol) of malic acid, stirring and mixing at room temperature, and adjusting the pH of the solution to between 7 and 8; wherein the molar ratio of the second complexing agent to the ruthenium source in terms of ruthenium is 1:1;
[0114] (3) Weigh 0.47 g (1.82 mmol) of tin tetrachloride and dissolve it in 10 ml of water, weigh 0.53 g (4.53 mmol) of succinic acid, stir and mix at room temperature, and adjust the pH of the solution to between 7 and 8; wherein the molar ratio of the third complexing agent to the tin source calculated in terms of tin is 2.5:1; and the molar ratio of the iridium source calculated in terms of iridium, the tin source calculated in terms of tin, and the ruthenium source calculated in terms of ruthenium is 6:3:1.
[0115] (4) mixing the three solutions of steps (1) to (3) and reacting them at 70° C. for 1 h;
[0116] (5) After cooling, spin-dry at 70°C and dry in an oven at 120°C for 8 h;
[0117] (6) After the catalyst is taken out and cooled, it is ground and laid flat on a porcelain boat. In an air atmosphere, the temperature is increased to 380°C at a rate of 2°C / min and maintained for 1 h.
[0118] (7) Cool to room temperature, add a certain amount of deionized water for ultrasonic washing and centrifugation (10000 rpm, 10 min), then wash with a 1:1 mixed solvent of ethanol and water and centrifuge for 3 times (pH test paper detection is neutral), and place the centrifuge tube containing the catalyst in a forced air drying oven (60°C) for 12 h. The obtained catalyst product is recorded as CAT-4.
[0119] XRF test analysis shows that the chemical composition of CAT-4 is Ir 0.6Ru 0.1 Sn 0.3 O 2 .
[0120] Example 5 Catalyst Ir 0.6 Ru 0.1 Sn 0.3 O 2 Preparation
[0121] The same preparation method as in Example 1 was used, except that:
[0122] The amount of citric acid in step (1) is 1.40 g (7.29 mmol); wherein the molar ratio of the first complexing agent to the iridium source is 2:1;
[0123] The amount of citric acid in step (2) is 0.20 g (1.04 mmol); wherein the molar ratio of the second complexing agent to the ruthenium source in terms of ruthenium is 1.7:1;
[0124] The calcination conditions were adjusted to: heating the mixture to 350°C at a heating rate of 2°C / min for 1 hour. The remaining steps were the same as those in Example 1. The obtained catalyst product was designated as CAT-5.
[0125] XRF testing shows that the chemical composition of CAT-5 is Ir 0.6 Ru 0.1 Sn 0.3 O 2 .
[0126] Example 6 Catalyst Ir 0.6 Ru 0.1 Sn 0.3 O 2 Preparation
[0127] The same preparation method as in Example 4 was used, and the specific difference from Example 4 was as follows:
[0128] (1) taking 20 mL (3.64 mmol) of potassium chloroiridate aqueous solution, weighing 0.55 g (3.64 mmol) of tartaric acid, stirring and mixing at room temperature, and adjusting the pH of the solution to between 7 and 8; wherein the molar ratio of the first complexing agent to the iridium source in terms of iridium is 1:1;
[0129] (2) Weighing 0.15 g (0.62 mmol) of ruthenium acetate and dissolving it in 5 ml of water, weighing 0.42 g (0.31 mmol) of malic acid, stirring and mixing at room temperature, and adjusting the pH of the solution to between 7 and 8; wherein the molar ratio of the second complexing agent to the ruthenium source in terms of ruthenium is 0.5:1;
[0130] (3) Weigh 0.47 g (1.82 mmol) of tin tetrachloride and dissolve it in 10 ml of water, weigh 0.32 g (2.73 mmol) of succinic acid, stir and mix at room temperature, and adjust the pH of the solution to between 7 and 8; wherein the molar ratio of the third complexing agent to the tin source calculated in terms of tin is 1.5:1; and the molar ratio of the iridium source calculated in terms of iridium, the tin source calculated in terms of tin, and the ruthenium source calculated in terms of ruthenium is 6:3:1.
[0131] (4) mixing the three solutions of steps (1) to (3) and reacting them at 70° C. for 1 h;
[0132] (5) After cooling, spin-dry at 70°C and dry in an oven at 120°C for 8 h;
[0133] (6) After the catalyst is taken out and cooled, it is ground and laid flat on a porcelain boat. In an air atmosphere, the temperature is increased to 380°C at a rate of 2°C / min and maintained for 1 h.
[0134] (7) Cool to room temperature, add a certain amount of deionized water for ultrasonic washing and centrifugation (10000 rpm, 10 min), then wash with a 1:1 mixed solvent of ethanol and water and centrifuge for 3 times (pH test paper detection is neutral), and place the centrifuge tube containing the catalyst in a forced air drying oven (60°C) for 12 h. The obtained catalyst product is recorded as CAT-6.
[0135] XRF test analysis shows that the chemical composition of CAT-6 is Ir 0.6 Ru 0.1 Sn 0.3 O 2 .
[0136] Example 7Ir 0.3 Ru 0.3 Sn 0.4 O 2 Preparation
[0137] The same preparation method as in Example 4 was used, except that:
[0138] The molar ratio of the iridium source calculated as iridium, the tin source calculated as tin and the ruthenium source calculated as ruthenium is 1:1.3:1, the potassium chloroiridate aqueous solution weighed in (1) is 10 mL (1.82 mmol), the ruthenium acetate weighed in (2) is 0.43 g (1.82 mmol), and the tin tetrachloride weighed in (3) is 0.63 g (2.42 mmol). The obtained catalyst product is recorded as CAT-7.
[0139] XRF test analysis shows that the chemical composition of CAT-7 is Ir 0.3 Ru 0.3 Sn 0.4 O2 .
[0140] Example 8Ir 0.6 Ru 0.1 Sn 0.3 O 2 Preparation
[0141] The same preparation method as in Example 4 was used, except that:
[0142] The calcination reaction conditions in step (6) are: calcination temperature is 450° C., and reaction time is 0.5 h. The obtained catalyst product is recorded as CAT-8.
[0143] XRF test analysis shows that the chemical composition of CAT-8 is Ir 0.6 Ru 0.1 Sn 0.3 O 2 .
[0144] Example 9Ir 0.6 Ru 0.1 Sn 0.3 O 2 Preparation
[0145] The same preparation method as in Example 4 was used, except that:
[0146] In step (1), step (2) and step (3), the pH of the solution is adjusted to 9. The obtained catalyst product is recorded as CAT-9.
[0147] XRF test analysis shows that the chemical composition of CAT-9 is Ir 06 Ru 01 Sn 03 O 2 .
[0148] Example 10Ir 0.6 Ru 0.1 Sn 0.3 O 2 Preparation
[0149] (1) Take 20 mL (3.64 mmol) of chloroiridic acid aqueous solution, take 0.13 g (0.62 mmol) of ruthenium trichloride and dissolve it in 5 ml of water, take Na 2 SnO 3 ·3H 2 0.48 g (1.82 mmol) of O is dissolved in 10 ml of water, 2.04 g (10.32 mmol) of citric acid is weighed, and after stirring and mixing at room temperature, the pH of the solution is adjusted to between 7 and 8; the molar ratio of the iridium source calculated as iridium, the tin source calculated as tin and the ruthenium source calculated as ruthenium is 6:3:1.
[0150] (2) reacting the mixed solution of step (1) at 70° C. for 1 h;
[0151] (3) After cooling, spin-dry at 70°C and dry in an oven at 120°C for 8 h;
[0152] (4) After the catalyst is taken out and cooled, it is ground and laid flat on a porcelain boat. In an air atmosphere, the temperature is increased to 330°C at a rate of 2°C / min and maintained for 2 h.
[0153] (5) Cool to room temperature, add a certain amount of deionized water for ultrasonic washing and centrifugation (10000 rpm, 10 min), then wash with a 1:1 mixed solvent of ethanol and water and centrifuge for 3 times (pH test paper detection is neutral), and place the centrifuge tube containing the catalyst in a forced air drying oven (60°C) for 12 h. The obtained catalyst product is recorded as CAT-10.
[0154] XRF test analysis shows that the chemical composition of CAT-10 is Ir 0.6 Ru 0.1 Sn 0.3 O 2 .
[0155] Comparative Example 1
[0156] A commercial iridium dioxide catalyst was used, purchased from Sigma Aldrich Company, with product number 206237, denoted as D1.
[0157] Comparative Example 2 Catalyst Ir 0.6 Ru 0.1 Sn 0.3 O 2 Preparation
[0158] The same preparation method as in Example 1 was used, except that:
[0159] No citric acid complexing agent is added in steps (1) to (3), and the other processes are the same as in Example 1; the obtained catalyst product is recorded as D2.
[0160] XRF test analysis shows that the chemical composition of D2 is Ir 06 Ru 01 Sn 03 O 2 .
[0161] Test Case
[0162] The catalyst particle size, BET specific surface area ... 0(M-OH / (M-OH+MO)) and electrochemical performance test data (initial overpotential, mV, denoted as G1; final overpotential, mV, denoted as G2; test current density 10 mA / cm 2 , Initial mass specific activity of the catalyst at 1.45 V vs. RHE, A / g (Ir+Ru) , denoted as M) are listed in the following Table 1.
[0163] Table 1
[0164]
[0165]
[0166] According to the data in Table 1, we can see that:
[0167] Compared with the catalysts D1 to D2 in Comparative Examples 1 to 2, the catalysts CAT-1 to CAT-10 prepared by the method provided by the present disclosure have a B 0 A larger value indicates that the surface M-OH content of CAT-1 to CAT-10 is higher; the overpotential G1 is lower and the mass specific activity M is higher, indicating that the oxygen evolution activity of CAT-1 to CAT-10 is higher; the amount of precious metal used in the catalyst prepared by the present invention is small, and the cost is reduced.
[0168] In addition, compared with D1 (existing commercial iridium dioxide catalyst), the catalyst provided by the present disclosure can effectively reduce the amount of precious metal iridium, and greatly improve the oxygen evolution activity of the catalyst while reducing the stability.
[0169] Compared with D2 (no complexing agent was added during the preparation process), the particle size of CAT-1 to CAT-10 is significantly smaller than that of D2, indicating that the addition of a complexing agent during the preparation process of the present disclosure can effectively improve the dispersion of the raw materials and reduce the particle size of the catalyst particles.
[0170] By comparing CAT-4 and CAT-6, it can be seen that within the range of the molar ratio of the first complexing agent to the iridium source calculated in iridium, the molar ratio of the second complexing agent to the ruthenium source calculated in ruthenium, and the molar ratio of the third complexing agent to the tin source calculated in tin, CAT-4 has a larger specific surface area, a smaller particle size, a lower overpotential G1, and a higher mass specific activity M, indicating that CAT-4 has a higher oxygen evolution activity.
[0171] By comparing CAT-4 and CAT-7, it can be seen that within the molar ratio range of the iridium source calculated in iridium, the tin source calculated in tin and the ruthenium source calculated in ruthenium disclosed in the present invention, CAT-4 has a smaller particle size, a lower overpotential G1, and a higher mass specific activity M, indicating that CAT-4 has a higher oxygen evolution activity.
[0172] By comparing CAT-4 and CAT-8, it can be seen that within the range of the calcination temperature and calcination time disclosed in the present invention, the B 0 The larger value, smaller particle size, lower overpotential G1, and higher mass specific activity M indicate that CAT-4 has higher oxygen evolution activity.
[0173] By comparing CAT-4 and CAT-9, it can be seen that within the preferred pH range of the present disclosure, CAT-4 has a smaller particle size, a lower overpotential G1, and a higher mass specific activity M, indicating that CAT-4 has a higher oxygen evolution activity.
[0174] By comparing CAT-1 and CAT-10, it can be seen that under the preferred material mixing order disclosed in the present invention, CAT-1 has a smaller particle size, a higher specific surface area, a lower overpotential G1, and a higher mass specific activity M, indicating that CAT-1 has a higher oxygen evolution activity.
[0175] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0176] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0177] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. An iridium ruthenium tin composite catalyst, characterized in that The iridium ruthenium tin composite catalyst contains iridium, ruthenium and tin elements, and the XRD spectrum of the iridium ruthenium tin composite catalyst only shows an amorphous peak package between 25 and 40 degrees.
2. The iridium ruthenium tin composite catalyst according to claim 1, wherein The O1s characteristic peak of the XPS spectrum of the iridium, ruthenium, and tin composite catalyst includes a MO characteristic peak and an M-OH characteristic peak, and B0 defined by the following formula (1) is any value between 0.4 and 0.5; B0=B1 / (B1+B2) Formula (1); Among them, B1 is the peak area of the M-OH characteristic peak in the XPS spectrum of the iridium ruthenium tin composite catalyst; B2 is the peak area of the MO characteristic peak in the XPS spectrum of the iridium ruthenium tin composite catalyst.
3. The iridium ruthenium tin composite catalyst according to claim 1, wherein The BET specific surface area of the iridium, ruthenium and tin composite catalyst is 60 to 80 m 2 / g, particle size is 3 to 8 nm.
4. The iridium ruthenium tin composite catalyst according to claim 1, wherein The chemical composition of the iridium ruthenium tin composite catalyst is Ir x Ru y Sn 1-x-y O2; wherein x is any value between 0.4 and 0.6, and y is any value between 0.1 and 0.
2.
5. The iridium ruthenium tin composite catalyst according to claim 1, wherein The XRD spectrum of the iridium, ruthenium and tin composite catalyst does not have the crystal plane diffraction peaks of IrO2, RuO2 and SnO2.
6. A method for preparing an iridium, ruthenium, and tin composite catalyst, characterized in that: The method comprises the following steps: S1, mixing an iridium source, a ruthenium source, a tin source, a complexing agent and water, and reacting the resulting mixture to obtain a first material; wherein the pH of the mixture is 5 to 9, and the complexing agent is selected from C4 to C8 organic polyacids and soluble salts of C4 to C8 organic polyacids; S2, separating the water in the first material to obtain an iridium ruthenium tin composite catalyst precursor; S3. calcining the iridium ruthenium tin composite catalyst precursor in an oxygen-containing atmosphere.
7. The method according to claim 6, wherein: Step S1 includes the following steps: S1-1, mixing the iridium source, the first complexing agent and water for the first time and adjusting the pH to 5 to 9, preferably 7 to 8, to obtain a first mixture; S1-2, mixing the ruthenium source, the second complexing agent and water for a second time and adjusting the pH to 5 to 9, preferably 7 to 8, to obtain a second mixture; S1-3, mixing the tin source, the third complexing agent and water for a third time and adjusting the pH to 5 to 9, preferably 7 to 8, to obtain a third mixture; S1-4, mixing the first mixture, the second mixture and the third mixture to obtain the mixed material.
8. The method according to claim 7, wherein: The iridium source is selected from one or more of chloroiridic acid and chloroiridic acid alkali metal salts; preferably, the chloroiridic acid alkali metal salt is selected from one or two of potassium chloroiridate and sodium chloroiridate; The ruthenium source is a soluble salt of ruthenium, preferably one or both of ruthenium trichloride and ruthenium acetate; The tin source is a soluble salt of tin and / or a soluble alkali metal stannate, preferably one or both of tin tetrachloride and sodium stannate.
9. The method according to claim 7, wherein: The first complexing agent, the second complexing agent and the third complexing agent are the same or different, and are independently selected from one or more of citric acid, tartaric acid, malic acid, succinic acid, sodium citrate, sodium tartrate, sodium malate and sodium succinate; Preferably, the molar ratio of the first complexing agent to the iridium source is 1.5 to 2.5:1, preferably 1.8 to 2.2:1; Preferably, the molar ratio of the second complexing agent to the ruthenium source calculated as ruthenium is 1 to 2:1, preferably 1.5 to 1.8:1; Preferably, the molar ratio of the third complexing agent to the tin source calculated as tin is 2 to 3:1, preferably 2.2 to 2.7:
1.
10. The method according to claim 6, wherein: In step S1, the molar ratio of the iridium source calculated as iridium, the tin source calculated as tin, and the ruthenium source calculated as ruthenium is (2-6):(1-5):
1.
11. The method according to claim 6, wherein: In step S1, the reaction conditions include: temperature of 50-80°C, preferably 60-70°C; reaction time of 0.5-4h, preferably 1-2h; Optionally, in step S1, the pH of the mixed material is 7 to 8; Optionally, a pH regulator is added to adjust the pH of the mixed material. Optionally, the pH regulator is selected from one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide and ammonia water.
12. The method according to claim 6, wherein: In step S3, the conditions for the calcination treatment include: a calcination temperature of 300 to 400° C., preferably 340 to 370° C.; and a calcination time of 1 to 3 hours.
13. The method according to claim 6, wherein: The method further comprises: washing the product obtained by the roasting treatment; the solvent used in the washing treatment is a mixed solution of alcohol and water, and the alcohol accounts for 10 to 95% by weight of the mixed solution, preferably 30 to 60% by weight; Preferably, the alcohol is selected from one or more of methanol, ethanol, n-propanol and isopropanol.
14. An iridium-ruthenium-tin composite catalyst prepared by the method according to any one of claims 6 to 13.
15. Use of the iridium, ruthenium, and tin composite catalyst according to any one of claims 1 to 5 and claim 14 in producing hydrogen by electrolysis of water.
Citation Information
Patent Citations
Catalyst for water electrolysis and preparation and application thereof
CN101733095A
Preparation method of iridium ruthenium-based oxygen evolution catalyst
CN114164458A
Preparation method of iridium tin catalyst as well as product and application thereof
CN115747859A
Anode for electrolytic evolution of chlorine
US20210238757A1
Cited By
Tin-doped iridium ruthenium solid solution oxide electrocatalyst as well as preparation method and application thereof
CN120797059A